A autenticidade na ética de Jean-Paul Sartre - Baranowske, Durval (2012)
The guidelines for this dissertation are to be found in two of Sartre s works, Being and Nothingness and Existentialism and Humanism. These two works form part of the composite body of texts written by Jean-Paul Sartre on ethics and authenticity. Other bibliographies have been drawn upon, with parts referred to at strategic points throughout this work. Ethics and authenticity in Sartre s philosophy form the basis for what I aim to examine, with three main areas of focus: uncovering what authenticity means to Sartre as a writer, how it can be an ethical concept and what its presence in human behaviour indicates. It would be meaningless to speak of authenticity if it were not for the notion of freedom always having Sartrean ontology at its core. To this end, the two initial chapters of this dissertation make an attempt to look more closely at the topic of ontology and to understand and recount the writer s main concerns with regard to authenticity and ethics. Following this, the major references comprise the commentators, all of whom have been duly cited in the final bibliography, and Sartre s literary works. And finally, ethics and authenticity would not have full meaning if it were not for the fact that they are grounded in existential ontology, because thinking of being, for Sartre, is thinking that one ought to be, which is being For-Itself, and reflecting on ethics means thematizing the original unity of its moral which lies in the authenticity of being and recognizing For-itself.